IMPLEMENTASI MANAJEMEN KONFLIK DALAM UPAYA PENCEGAHAN DAN PENANGGULANGAN TINDAK KEKERASAN DI SMPN 59 KOTA BANDUNG - Pramesti Salma Ihsandina Suherlan; Wahyu Hidayat (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2023)
According to the Ministry of Women’s Empowerment and Child Protection in Indonesia there were 6.139 cases of violence that occured in the home, school, and community environment. The purpose of this study was to determine the implementation of conflit management in efforts to prevent and control acts of violence within the education unit. The subject of this study is counseling teacher at SMPN 59 Bandung City. This reasearch method used a qualitative field study approach by collecting data through interviews, observation, and documentation. The result of this study showed that violence occured only in the form of verbal abuse caused by jokes. Prevention efforts are carried out by participating in training, the declaration of Roots Day, and forming a agent of changes’ team in each class. The coping procedure goes through several stages, namely subject teacher, homeroom teachers, guidance and counseling teachers, and staff students. Therefore, SMPN 59 is able to implement conflict management in an effort to prevent and deal with acts of violence within the education sector